Biotype composition and virulence distribution of wheat curl mite in the North Central United States - Khalaf, Luaay Kahtan (Kansas State University, 2018)
The wheat curl mite, Aceria tosichella (Keifer), is an important global pest of bread wheat, Triticum aestivum L. Chronic and often severe reductions of winter wheat yield due to A. tosichella infestations have occurred in North America and all other wheat-production areas for over five decades. Moreover, A. tosichella is the only vector which transmits the three most important wheat viruses in the Great Plains, which are Wheat Streak Mosaic Virus (WSMV), the most economically important wheat virus in North America; Triticum Mosaic Virus (TriMV) and High Plains Wheat Mosaic Virus (HPWMoV). Mite infestation alone causes stunted, chlorotic plants in susceptible wheat varieties. To date, mite resistant wheat cultivars have been the only sufficient method to control A. tosichella. The discovery of new genes for A. tosichella resistance and their introgression into wheat cultivars are essential steps to combat the development of new and/or different A. tosichella biotypes which can develop to overcome resistance genes. Both A. tosichella biotype 1 and 2 exist in U. S. Great Plains wheat producing areas. Elucidating and predicting A. tosichella population composition changes based on climatic and geographic variables is a key to continued effective mite management. Experiments were conducted to: 1) assess A. tosichella virulence in mites collected from 25 sample sites in six states to wheat plants harboring the Cmc2, Cmc3 and Cmc4 mite resistance genes and the Wsm2 WSMV resistance gene in 2014 and 2015, and determine the distribution of WSMV, TriMV and HPWMoV present in mites collected; 2) assess A. tosichella biotype composition using internal transcribed spacer 1 (ITS1) and cytochrome oxidase I (COI) polymorphisms; 3) use generalized additive modeling to capture the spatio-temporal factors contributing to the prevalence of A. tosichella biotypes 1 and 2; and 4) screen Kansas advanced breeding lines for resistance to A. tosichella biotypes 1 and 2. Results indicated that A. tosichella collected from 92% of the sample area were virulent to susceptible Jagger wheat plants with no Cmc resistance genes; that mites from 36% of the sample area were virulent to the Cmc2 gene, and that mites collected from 24% of sample area were virulent to Cmc3. Mite populations from only 8% of the sample sites exhibited virulence to plants containing Cmc4 + Wsm2 or Cmc4. The WSMV virus was predominant and present in 76% of all mites sampled. HPWMoV and TriMV were less apparent and present in 16% and 8% of all mites sampled, respectively. These results will enable breeders to increase the efficiency of wheat production by releasing wheat varieties containing A. tosichella resistance genes that contribute to reducing virus transmission. Results of spatio-temporal factor modeling provide new, more accurate information about the use of ground-cover and precipitation as key predictors of biotype prevalence and ratio. Experiments to determine if Kansas State University advanced breeding lines contain A. tosichella resistance found no resistance to biotype 1, resistance to biotype 2 in breeding lines AYN3-37 and AYN3-34; and moderate resistance to biotype 2 in breeding lines AYN2-28 and AYN2-36. The demonstrated correlation between reduced A. tosichella population size and avirulence; characterization and prediction of the A. tosichella biotype composition; and the identification of new sources of A. tosichella resistance in wheat can help entomologists and wheat breeders increase wheat production efficiency by releasing additional wheat cultivars containing A. tosichella resistance genes.
Keywords: Wheat curl mite; Virulence; Cmc genes; Biotype composition; Winter wheat; Arthropod-plant interaction